1977
DOI: 10.1002/j.1552-4604.1977.tb05645.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Trial of Single‐Dose Versus Twice‐Daily Sisomicin in Bacteriuric Patients

Abstract: Sisomicin was administered as a single daily intramuscular injection (160 mg) or as two daily injections (80 mg) to 50 patients with bacteriuria superimposed on chronic urologic diseases in a randomized controlled fashion. The administration of two daily doses was significantly more effective (P less than 0.01) in achieving cure than the injection of a single daily dose. The renal function, as expressed by creatinine clearance, became impaired significantly more often (P less than 0.05) in the patients receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…All patients in three studies [35,38,41] and the majority of patients in one study [40] underwent primary surgical intervention for the treatment of intra-abdominal infections. All patients in two studies [33,44] and the majority of patients in two other reports [46,49] had urinary tract infections. All patients in two studies [50,53] and more than half of all patients in another [37] were neutropenic.…”
Section: Resultsmentioning
confidence: 89%
“…All patients in three studies [35,38,41] and the majority of patients in one study [40] underwent primary surgical intervention for the treatment of intra-abdominal infections. All patients in two studies [33,44] and the majority of patients in two other reports [46,49] had urinary tract infections. All patients in two studies [50,53] and more than half of all patients in another [37] were neutropenic.…”
Section: Resultsmentioning
confidence: 89%
“…We identified 25 trials1 4 5 7 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 and used 21 of them, with a total of 3091 patients, in the meta-analysis (table 1). We excluded four studies, three because the total daily dose of aminoglycosides was different in the two treatment arms32 33 34 and the fourth because aminoglycosides were used for prophylaxis for colorectal surgery 31.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the specific drug used bore no significant relation to the relative risk of failure in the two treatment arms of the study. An exception was the one study of sisomicin, which is not commercially available 5. Only this trial showed a significantly better efficacy with multiple daily doses (fig 1).…”
Section: Heterogeneity Of Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total 16 publications were included [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The publications were searched for electronically through the Index Medicus and through lists of references.…”
Section: Methodsmentioning
confidence: 99%